Effects of plant species and harvesting system on grassland production in northern Finland - Nissinen, Oiva; Hakkola, Heikki (Agricultural and Food Science, 1995)
The dry matter yields and forage quality of seven grassland plant species and mixed stands which included three cutting regimes (pasture 4-5 cuts, silage 2-3 cuts, hay and aftermath) were studied at two locations in northern Finland, Ruukki (64°40’N) and Rovaniemi (66° 35’N). Increased cutting frequency lowered the total dry matter yields of all plant species. Production of timothy (Phleum pratense L.) and smooth brome grass (Bromus inermis L.) swards was significantly reduced by taking four or five cuts instead of one or two cuts. Meadow fescue (Festuca pratensis Huds.) and meadow grass (Poa pratensis L.) showed only a minor interaction with harvesting regimes and were less affected by the cutting frequency. The increased cutting frequency raised the crude protein content, this causing the highest protein yields despite the smaller dry matter yields. The inclusion of red clover in seed mixtures had a favourable effect on the crude protein content of grass swards. Stands of sown plants decreased and the proportion of weeds in yields increased with time, reflecting the suitability of plant species to various cutting regimes. Meadow fescue and meadow grass with rapid regrowth had a positive effect on sward density and also caused less invasion of weeds when the cutting frequency was increased.